Examining the knowledge of basic concepts of children starting primary education - UYANIK, GÜLDEN (My University, 2009)
This study aims to examine the knowledge of basic concepts of children starting primary education. The sampling for the study is constituted by total 183 children, 89 girls and 94 boys. The knowledge about the concepts of the children making up the sampling was evaluated using Boehm's Test of Basic Concepts (Boehm-3). Moreover, the Family Information Forms, prepared by the researcher, were used for the demographic information regarding the children. No difference was determined in the knowledge of concepts of the children according to gender. When the levels of benefiting from the preschool education were evaluated, it was observed that the concept points of the children increased as the period for benefiting from the preschool education got longer and the difference between the groups was found to be significant. A significant correlation was found between the educational levels of both mothers and fathers and the concept points of the children and it was found that the concept points of the children increased as the educational level of the parents got higher. Moreover, the difference between the concept points of the children according to the socioeconomic levels of the families was found to be significant. © 2009 Taylor & Francis.
Keywords: Concept development; Family; Preschool education; SES